THE IMPACT OF SUPERIOR SUPPORT ON BUILDING MOTIVATION AND WORK COMMITMENT: THE MALAYSIAN EXPERIENCE - Young Shang Yi; Zahimi Zainol Abidin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The success of an organization greatly depends on having a highly motivated and committed workforce. A key factor influencing employee motivation and work commitment is the level of managerial support provided by supervisors and upper management. This study investigates the effects of superior support on building motivation and work commitment among employees in the Malaysian context. Utilizing a mixed-methods approach, the research combines quantitative and qualitative data collection and analysis. A survey was conducted with 345 employees across various industries in Malaysia to measure the relationship between superior support, employee motivation, and work commitment. This was complemented by in-depth interviews with 10 managers to gain deeper insights into how higher levels of support influence employee attitudes and behaviors. The findings reveal that superior support, encompassing both instrumental and emotional support, has a significant positive impact on employee motivation and commitment. Employees who perceive higher levels of support from their superiors tend to exhibit greater intrinsic motivation, as well as stronger affective and normative commitment to the organization. Qualitative data provides evidence that superior support fosters a sense of value and belonging among employees, which, in turn, strengthens their dedication and willingness to exert effort. This study contributes to the literature on human resource management and organizational behavior by elucidating the critical role of leadership support in shaping a motivated and committed workforce, particularly within the Malaysian cultural context. The results offer practical insights for managers and policymakers on strategies to enhance employee motivation and retention through the provision of superior support. Future research directions and study limitations are also discussed.